STRUKTUR PUISI DAN KETIDAKLANGSUNGAN EKSPRESI DALAM LIRIK LAGU KARYA FUNKY MONKEY BABYS - Susila, I Putu Dipa Pranata; Anak Agung Ayu Dian Andriyani; Made Henra Dwikarmawan Sudipa (Jurnal Daruma : Linguistik, Sastra dan Budaya Jepang, 2023)
This study aims to describe the structure and indirectness of any expressions contained in the lyrics of the song Funky Monkey Babys. The theory used in this study is a theory related to research, including the theory of the structure of poetry and the theory of semiotics. The research method used is a qualitative descriptive method. In this thesis the data are in the form of song lyrics Ato Hiotsu, Mou Kimi Ga Inai, Tabidachi, Namida, and Taisetsu. The data were analyzed using the theory of poetry structure and the theory of indirectness of expression. The results obtained from this research are; in the structure of the poetry of the songs Ato Hiotsu, Mou Kimi Ga Inai, Tabidachi, Namida, and Taisetsu found diction, figure of speech, and imagery with the theme of love, and the message don't give up. In the discontinuity of the expressions in the songs Ato Hiotsu, Mou Kimi Ga Inai, Tabidachi, Namida, and Taisetsu found a change in meaning and the Blank symbol which is more widely used. Keywords: Structure, Song, Lyrics, Unsustainability of Expression